Understanding irradiation-induced nanoprecipitation in zirconium alloys using parallel TEM and APT - Harte, A; Prasath Babu, R; Hirst, C; Martin, T; Bagot, P; Moody, M; Frankel, P; Romero, J; Hallstadius, L; Darby, E; Preuss, M (Elsevier, 2018)
We investigate nano-scale irradiation-induced precipitation in a ZrSnFeCrNi-alloy (Zircaloy-2) by combining atom probe tomography (APT) for chemical detail with scanning transmission electron microscopy (STEM) and high resolution energy dispersive X-ray (EDX) spectroscopy for wider context and complimentary and correlative TEM diffraction techniques for crystallographic relationships. We find that Fe and Cr-rich nano-rods precipitate in Zircaloy-2 following proton irradiation at 350 °C to a low dose of ∼2 dpa. The long-axis of the nano-rods are aligned in a direction 12–15° from the Zr matrix , align in the basal plane and are of width 1.5–5 nm. Smaller rods are of APT-determined composition Zr4(Fe0.67Cr0.33), tending towards Zr3(Fe0.69Cr0.31) as the rod volume increases to > ∼400 nm3, in agreement with STEM-EDX determination of composition resembling that of Zr3Fe with Cr replacing some of the Fe. The Fe/Cr ratio has been shown to increase with distance from the nearest partially-dissolved Zr(Fe,Cr)2  phase particle. The nucleation of nano rods has implications for macroscopic irradiation-induced deformation phenomena, irradiation-induced hardening and the evolution of dislocation loops and other defects.